Pengembangan Kemampuan Hafalan Al-Qur’an Siswa Melalui Metode Pembelajaran Tahfidz - Khoirunnisa; Yazidul Busthomi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe the concept of improving Al-Qur'an memorization ability, examine the effectiveness of tahfidz methods, and formulate efforts to optimize the memorization program based on theoretical studies and previous research findings. The study employs a case study method with a descriptive qualitative approach, conducted at Lembaga Tahfidz Al-Islami Ganjaran Malang through observation, interviews, and documentation. Data were obtained from the school principal, teachers, students, and supporting documents. The research focus includes planning, implementation, talaqqi, tikrar, sima'i, muraja'ah methods, evaluation, obstacles, as well as the roles of teachers and parents. The results show that the improvement of Al-Qur'an memorization ability is influenced by appropriate learning methods, such as the Qiroati method, tikrar, talaqqi, memorization deposit, and structured muraja'ah. Internal student motivation, the role of tahfidz teachers, and program implementation consistency also significantly affect memorization quality. The literature review reveals obstacles such as differences in individual abilities and lack of consistent independent muraja'ah. Based on the findings, this study recommends strengthening the guidance system, mentoring, and continuous program evaluation to optimize students' Al-Qur'an memorization achievement